2009
DOI: 10.1080/00016340802657561
|View full text |Cite
|
Sign up to set email alerts
|

Reasons of refusal and drop out in a follow up study involving primigravidae in Pakistan

Abstract: Refusal to participate and drop out from the research program are two significant factors hindering the smooth flow of a study. In Pakistan, the major reason for the refusal by the protocol-eligible pregnant women for participating in a research program is the unwillingness of the family members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Inconvenience was mentioned in 25 articles as a reason for non‐participation , ranked as the top three reasons fourteen times , and ranked first in four articles . Examples of inconveniences included not having enough time to participate in research, transport issues or a long distance to the research site .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inconvenience was mentioned in 25 articles as a reason for non‐participation , ranked as the top three reasons fourteen times , and ranked first in four articles . Examples of inconveniences included not having enough time to participate in research, transport issues or a long distance to the research site .…”
Section: Resultsmentioning
confidence: 99%
“…Additional reasons given for non-participation were costs [44,58,69,103,111], cultural insensitivity [37,101], fear of false-positive test results after participation in HIV research [36,44,45,50,59,86,93,94], fear of knowledge of health status [19,28,30,54,68], insufficient compensation [21,43], invasive procedures, [1,20,30,39,54,78,87,106] lack of interest [30,34,37,61,86,95,102,104,105,109], lack of clarity [1,30,37,51,52,91,111], not willing to comply to terms of research [55,68,…”
Section: Other Reasons For Non-participationmentioning
confidence: 99%
“…As it was not possible in this current study to investigate the reasons for not participating, we can only speculate on potential drivers for a low participation rate. For example, there could be psychological factors with individuals who fear needles or medical exams [ 28 ], or who refuse to know from which disease they may suffer [ 29 ]. Other reasons include the lack of timely feedback on study findings to participants due to the reluctance of researchers to reveal relevant information before an international publication.…”
Section: Discussionmentioning
confidence: 99%
“…The participation rate in this field research conducted in the rural area of Eskisehir Province was detected as 76.1 percent. The rate of participation in epidemiological studies reportedly ranged between 48, and 78.5 percent [10, 11, 12, 13]. In a study performed in Turkey, the researchers reported that 11% of the individuals closed the door to the interviewers without listening them, and 57% of the individuals agreed to participate in the research after listening the information given to them [14].…”
Section: Discussionmentioning
confidence: 99%
“…In a study performed in the UK, as the most important reasons for not participating in the study were expressed by the participants as their inability to contribute to the researches, their reluctance to entertain strangers at their homes, and their unwillingness to respond to the questions related to their personal life [11]. In an investigation performed in Pakistan, as the most important reasons for non-participation, objections of the family members, and fear from interventional applications of the research outcomes were indicated [13]. In a study realized in Italy, the participants stated their reason for non-participation in cohort studies as unnecessarily long study periods [16].…”
Section: Discussionmentioning
confidence: 99%